2007
DOI: 10.1121/1.2404625
|View full text |Cite
|
Sign up to set email alerts
|

The binaural performance of a cross-talk cancellation system with matched or mismatched setup and playback acoustics

Abstract: Cross-talk cancellation is a method for synthesising virtual auditory space using loudspeakers. One implementation is the "Optimal Source Distribution" technique [T. Takeuchi and P. Nelson, J. Acoust. Soc. Am. 112, 2786-2797 (2002)], in which the audio bandwidth is split across three pairs of loudspeakers, placed at azimuths of ±90°, ±15°, and ±3°, conveying low, mid and high frequencies, respectively. A computational simulation of this system was developed and verified against measurements made on an acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Such least-squares optimization can be based on measured transfer functions, which lifts many of the constraints on source positions imposed by the analytical approaches and is referred to herein as pressure matching (PM). PM represents a logical extension of binaural techniques such as crosstalk cancellation (e.g., Bai and Lee, 2006;Akeroyd et al, 2007) over a larger spatial region by allowing the definition of complex pressures, for instance, to define a plane wave propagating across the bright zone.…”
Section: Introductionmentioning
confidence: 99%
“…Such least-squares optimization can be based on measured transfer functions, which lifts many of the constraints on source positions imposed by the analytical approaches and is referred to herein as pressure matching (PM). PM represents a logical extension of binaural techniques such as crosstalk cancellation (e.g., Bai and Lee, 2006;Akeroyd et al, 2007) over a larger spatial region by allowing the definition of complex pressures, for instance, to define a plane wave propagating across the bright zone.…”
Section: Introductionmentioning
confidence: 99%
“…HRTFs represent the directional-dependent transfer functions of sound to both ears (Blauert, 2001). In virtual acoustics, such as in SHB processing and cross-talk-cancellation (Akeroyd et al, 2007;Bauer, 1961;Møller, 1989), HRTFs may affect both the recording and the playback stage of sound reproduction. Møller et al (1996) demonstrated that there is no difference between localization in real life and when listening to recordings, if these are made using the subjects' own ears, and if headphones are equalized to their individual ears.…”
Section: E Individuality Of Hrtfsmentioning
confidence: 99%
“…Distinguishing the points for system setup and performance evaluation is important for ensuring independence, especially when only one set of responses (from one measurement run) is available, or when analytical responses are used. Performance predictions based on the setup points lead to overestimated contrast that is never attainable in practice [12].…”
Section: Acoustic Contrast Control (Acc) Methodsmentioning
confidence: 99%